Recommendations for Strengthening Delivery of Nutrition Services through the Platform of Community Action for Health and Nutrition in Nagaland, India - World Bank Group (World Bank, Washington, DC, 2019)
In the state of Nagaland, stunting prevalence among under-five children decreased from 39 to 29 percent over the decade between the National Family Health Surveys done in 2005-06 and 2015-16 andis lower than the national average of 38 percent. During the same period, under-five prevalenceof wasting decreased marginally from 13 to 11 percent.1 However, within the state of Nagaland,there is significant variation in nutritional status between districts. For instance, stunting rates among under-five children range between a 19 percent in Tuensang district and 42 percent inKiphire district; wasting prevalence ranges between 2 percent in Mokokchung and 21 percent in Mon.Further, a third of all pregnant women in Nagaland are anemic and about 12 percent of all women aretoo thin. Thus, despite improvements in nutritional status by some measures, undernutrition in women and children remains a significant challenge.